2020
DOI: 10.1108/jfbm-04-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

Retaining the adolescent workforce in family businesses

Abstract: PurposeThe purpose of this study is to critically explore the linkage between adolescent work, parent–child relationships and offspring career choice outcomes in a family business context. It examines the aforementioned in light of the stay/go decision faced by adolescent family members.Design/methodology/approachFindings are derived from semi-structured interviews with 15 individuals from five Italian families operating family catering businesses in Yorkshire (UK). The approach represents a sample spanning fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…This was also evident in Filipino and Chinese-owned family businesses [38]. They experienced transitioning from lower-ranked job positions to higher ones like being appointed as business owners or inheritors [39]. The business is believed to be strengthened when family members and children at a young age are involved [34].…”
Section: Emerging Theme 1: Family Business Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also evident in Filipino and Chinese-owned family businesses [38]. They experienced transitioning from lower-ranked job positions to higher ones like being appointed as business owners or inheritors [39]. The business is believed to be strengthened when family members and children at a young age are involved [34].…”
Section: Emerging Theme 1: Family Business Involvementmentioning
confidence: 99%
“…When compared to Chinese-Filipino parents, Filipino mothers, and fathers are more supportive and lenient when it comes to their children's career choices. In published studies, researchers reported that children tend to sacrifice their personal goals especially if they spent long years in their family workplace [39]. Researchers also correlated the difficulty of exiting a family business with the level of children's involvement.…”
Section: Emerging Theme 2: Strong Family Relationshipsmentioning
confidence: 99%